Analisis strategi bertahan Indonesia vs Autralia leg ke-2 kualifikasi piala dunia 2026 - Moh Raziqi Luthfi; Rizki; Ahmad (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
This study aims to analyze the defensive strategies used by the Indonesian National Team against the Australian National Team in the second leg of the 2026 FIFA World Cup Asian Qualifiers. The research employed a descriptive quantitative method, with data obtained through observation of match video recordings. The recordings were analyzed using manual coding, where each instance of defensive play was coded according to operational definitions: high pressing involves pressing opponents near their defensive line, middle pressing occurs in the midfield area, and low pressing involves waiting for the opponent in the defensive zone while maintaining a compact formation. Observations were conducted by a primary observer experienced in football tactical analysis, and the reliability of the observations was ensured through an inter-rater test with an additional observer to confirm coding consistency. The analysis aimed to identify and calculate the success rate of each defensive style. The results showed that low pressing was the most effective strategy with a success rate of 64.2%, followed by high pressing at 63.5%, while middle pressing only reached 42.8%. These findings indicate that low pressing aligns best with the Indonesian National Team's playing style, emphasizing discipline, compactness, and effectiveness in executing quick counterattacks. Therefore, the implementation of appropriate defensive strategies can enhance overall game stability and effectiveness.